High School Students' Misconceptions on Materials of Temperature and Heat Using Three-Tier Diagnostic Tests Assisted by Live Worksheets - Tita Tanggira, Lambang subagiyo, Abdul Hakim (Berkala Ilmiah Pendidikan Fisika, 2022)
This study aims to discover the misconceptions experienced by high school students on the material of temperature and heat. This type of research is descriptive quantitative. The sample of this research is XI science students at MAN 1 Samarinda and SMA Negeri 2 Samarinda, with 80 students. Research data were collected using tests. This type of test is a three-tier diagnostic test with three levels of answer choices, including questions and answer choices, reasons for answering, and confidence in answering. Overall, the results showed that students had misconceptions of 43.4%, which were classified as medium category misconceptions. Based on the misconceptions obtained, The misconceptions identified in the overall temperature and heat material are 43,36%, the percentage of understanding concepts is 34.75%, the percentage of only guessing is 8.67%, and the percentage of only guessing not understanding concepts is 13.08%. The percentage of misconceptions obtained includes the concepts of temperature and heat in the medium category level.